Task-based Language Teaching to Develop Malay Language Speaking Skills of Primary 5 Singaporean Students - Omar, Zainaba; Jamaludin, Norliza; Arshad, Mahzan (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2021)
The purpose of this study is to examine the effectiveness of task-based language teaching approach for improving speaking skills, focusing on fluency, use of appropriate language structure and vocabulary for primary schools in Singapore. This study is also to find out whether the task-based language teaching model can increase students' motivation level, confidence, and ability to speak Malay. This quasi-experimental non-equivalent groups pre-post-tests design study was conducted in Singapore, involving primary 5 pupils from two different schools. The treatment group comprised of 30 students while 22 students were included in the control group. The treatment group used the task-based language teaching model and the control group used conventional approaches. The treatment and control groups underwent oral pre-test before task-based language teaching approach and conventional approaches, respectively. Five task-based language teaching lessons were carried out for five weeks before post-test was administered using pictures for the treatment group. The control group took the same post-test after the conventional approach. The treatment group also completed survey questions before and after task-based language teaching approach. Findings show that there were significant differences between the pre- and post-tests scores for fluency, vocabulary, and language among students in the treatment group. For the control group, there were no significant differences between pre- and post-test scores for fluency, vocabulary, and use of language. However, when the post-test scores of both groups were compared, the results show only significant differences for fluency but not for vocabulary and language. The descriptive results show improvement in motivation and confidence after using task-based language teaching approach. Based on the findings, the researchers recommend that task-based approach be given more attention in Malay Language classes though they also suggest that further research is needed to explore more in the effectiveness of task-based programs for other levels.